Effect of modulation p-doping on the optical properties of quantum dot laser structure - Hasbullah, Nurul Fadzlin; David, J. P. R.; Mowbray, D. J. (2010)
Temperature dependence electroluminescence (EL) measurements have been performed on In(Ga)As/ GaAs quantum dot (QD) structures with varying amounts of modulation p-doping. It is found that the IEL decreases with increasing temperature with the size of reduction decreases with increasing doping level. Activation energies derived from the temperature dependence results shows that the values increases with increasing doping. This is attributed to an increased Coulombic attraction between the extrinsic holes and injected electrons.